2021
DOI: 10.1002/jcp.30361
|View full text |Cite
|
Sign up to set email alerts
|

miR‐144‐3p ameliorates the progression of osteoarthritis by targeting IL‐1β: Potential therapeutic implications

Abstract: The pro‐inflammatory cytokine interleukin 1 beta (IL‐1β) plays a critical role in osteoarthritis (OA) disease pathogenesis. MicroRNA (miRNA) activity is related to inflammation in OA and some miRNAs specifically regulate IL‐mediated degradation of cartilage type II collagen. Previous studies have indicated that miR‐144‐3p is a useful target in the regulation of pro‐inflammatory cytokines in different diseases. However, the role of miR‐144‐3p in OA is unclear. In this study, we observed a negative correlation b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 55 publications
1
27
0
Order By: Relevance
“…Western blot and ELISA assays revealed that nesfatin-1 increased cellular and secreted IL-1β protein expression ( Figure 2B – 2D ). The PI3K and Akt signaling cascade mediates IL-1β expression during the progression of arthritis [ 25 ]. Treating OASFs with either a PI3K inhibitor (Ly294002) or an Akt inhibitor (Akti) markedly antagonized nesfatin-1-induced IL-1β synthesis ( Figure 3A and 3C ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Western blot and ELISA assays revealed that nesfatin-1 increased cellular and secreted IL-1β protein expression ( Figure 2B – 2D ). The PI3K and Akt signaling cascade mediates IL-1β expression during the progression of arthritis [ 25 ]. Treating OASFs with either a PI3K inhibitor (Ly294002) or an Akt inhibitor (Akti) markedly antagonized nesfatin-1-induced IL-1β synthesis ( Figure 3A and 3C ).…”
Section: Resultsmentioning
confidence: 99%
“…The mediation of IL-1β synthesis by miRNAs is crucial in the progression of OA [ 25 ]. Our search of online databases for miRNA target prediction data suggested that the three prime untranslated region (3′-UTR) of IL-1β mRNA includes 19 promising candidate miRNAs ( Figure 5A and 5B ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations